Smart Bandage Based on Molecularly Imprinted Polymers (MIPs) for Diclofenac Controlled Release - Ortensia Ilaria Parisi; Mariarosa Ruffo; Luca Scrivano; Rocco Malivindi; Antonio Vassallo; Francesco Puoci (MDPI AG, 2018)
The aim of the present study was the development of a “smart bandage” for the topical administration of diclofenac, in the treatment of localized painful and inflammatory conditions, incorporating Molecularly Imprinted Polymers (MIPs) for the controlled release of this anti-inflammatory drug. For this purpose, MIP spherical particles were synthesized by precipitation polymerization, loaded with the therapeutic agent and incorporated into the bandage surface. Batch adsorption binding studies were performed to investigate the adsorption isotherms and kinetics and the selective recognition abilities of the synthesized MIP. In vitro diffusion studies were also carried out using Franz cells and the obtained results were reported as percentage of the diffused dose, cumulative amount of diffused drug, steady-state drug flux and permeability coefficient. Moreover, the biocompatibility of the developed device was evaluated using the EPISKIN™ model. The Scatchard analysis indicated that the prepared MIP is characterized by the presence of specific binding sites for diclofenac, which are not present in the corresponding non-imprinted polymer, and the obtained results confirmed both the ability of the prepared bandage to prolong the drug release and the absence of skin irritation reactions. Therefore, these results support the potential application of the developed “smart bandage” as topical device for diclofenac sustained release.